Thymoquinone alleviates the accumulation of ROS and pyroptosis and promotes perforator skin flap survival through SIRT1/NF-κB pathway - Yang, Jianxin; Zhang, Haojie; Ni, Libin; He, Jun (Frontiers in Pharmacology, 2025)
Perforator flap transplantation is an important technique in flap reconstructive surgery, but flap necrosis limits its clinical effectiveness. Thymoquinone (TQ), a natural bioactive plant quinone found in black seed, exhibits anti-inflammatory, angiogenic, and antimicrobial properties. This study investigates the therapeutic effects of TQ in a perforator flap model through in vivo and in vitro experiments. Human umbilical vein endothelial cells (HUVECs) were treated with Tert-butyl Hydroperoxide (TBHP) to simulate an in vitro flap model and were then treated with TQ. In vivo experiments used a rat perforator flap model, and vascularization was assessed using Doppler ultrasound on days 3 and 7 after flap creation. On day 7 post-surgery, flap samples were collected to evaluate vascularity, reactive oxygen species, apoptosis and pyroptosis. Network pharmacology analysis was conducted to identify relevant signaling pathways, and molecular docking techniques were used to predict potential target binding sites. In vitro results showed that both TQ treatment and NLRP3 inhibitors reduced the expression of pyroptosis-related proteins. In vivo results indicated that the TQ-treated group had increased flap survival area, blood flow intensity, and microvascular density, while oxidative stress, apoptosis, and pyroptosis levels were reduced. Angiogenesis was enhanced, and expression of the SIRT1 protein was increased, while the p-P65/NF-κB/NLRP3 pathway was downregulated. After treatment with a SIRT1 inhibitor, flap survival rate and angiogenesis were reduced. These findings suggest that TQ improves perforator flap survival by inhibiting the NF-κB/NLRP3 pathway and promoting angiogenesis.